Spanish Adaptation of the Dimensional Apathy Scale (DAS) in Amyotrophic Lateral Sclerosis - Salas, Teresa; Radakovic, Ratko; Rodriguez-Castillo, Víctor; Marín, Saúl; Chaverri, Delia; Rodriguez-Santos, Francisco (Frontiers in Neurology, 2020)
Aim To adapt, translate and utilise the Dimensional Apathy Scale (DAS) in Amyotrophic Lateral Sclerosis (ALS) to the Spanish population. Method 104 ALS patients (67 of their caregivers) and 49 controls were recruited. Participants completed the Spanish translated DAS, Geriatric Depression Scale- Short form. Patients were also administered the ALS Functional Rating Scale-Revised (ALSFRS-R). Caregivers additionally completed the informant/caregiver-rated Spanish translated DAS. The DAS was translated to Spanish using a back-translation method. Test-retest and internal consistency reliability was examined. Divergent validity was assessed by comparing the DAS to the depression scale (GDS-15). Principal Component Analysis (PCA) was applied to explore the substructure of the Spanish DAS. Results The internal consistency reliability of self-rated Spanish DAS was 0.72 and of the informant/caregiver-rated Spanish DAS was 0.84. Correlations between self-rated DAS subscales and GDS-15 was non-significant, with a good test-retest reliability. PCA analysis showed a similar substructure to the original DAS. ALS patients had significantly higher Initiation apathy than controls. Additionally, ALS patient informant/caregiver-rated DAS Emotional apathy was significantly higher than the self-rated, with no significant differences were observed in the Executive and Initiation subscales. No association was found between DAS and functional impairment using the ALS Functional Rating Scale (ALSFRS-R). Conclusion The Spanish translation of the DAS is valid and reliable for use in assessing multidimensional apathy in the Spanish population. Availability of the Spanish DAS will allow for future research to explore different apathy subtypes and their impact in ALS and other conditions.